KAIDAH PENAMAAN LEKSEM BENDA-BENDA KECIL (ISM TAṢGĪR) DALAM KAMUS AL-MUNAWWIR ARAB-INDONESIA (ANALISIS MORFOSEMANTIK) - Muhammad Yunus Anis, Arifuddin (Arabic Literature Department, 2020)
This article will generally examine the naming convention of small objects lexemes (ism tagīr) in the Al-Munawwir Arabic-Indonesian dictionary. The approach used in this study is a linguistic approach, especially closely related to morphosemantics. In this case, the morphosemantic study involves the study of the structure and meaning of the lexeme in relation to small objects or what is commonly referred to in Arabic as ism taṣgīr. The research method consists of three important stages, such as: (1) the data collection and analysis using the observation method of linguistic units in the form of